2018
DOI: 10.1371/journal.pone.0204574
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of urban scaling: Evidence from Brazil

Abstract: During the last years, the new science of cities has been established as a fertile quantitative approach to systematically understand the urban phenomena. One of its main pillars is the proposition that urban systems display universal scaling behavior regarding socioeconomic, infrastructural and individual basic services variables. This paper discusses the extension of the universality proposition by testing it against a broad range of urban metrics in a developing country urban system. We present an explorati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 29 publications
6
69
0
6
Order By: Relevance
“…Those cases behave differently from the pattern uncovered by our approach. This result (10) was also obtained by Bettencourt et al [47] using a slightly different approach. The result (10) also suggests that if F ext > 0 and b i > 1, which means that both the intercept parameter (global growth) and the population are growing in time, then β i will always be greater than the global exponent β T .…”
Section: Plos Onesupporting
confidence: 82%
See 3 more Smart Citations
“…Those cases behave differently from the pattern uncovered by our approach. This result (10) was also obtained by Bettencourt et al [47] using a slightly different approach. The result (10) also suggests that if F ext > 0 and b i > 1, which means that both the intercept parameter (global growth) and the population are growing in time, then β i will always be greater than the global exponent β T .…”
Section: Plos Onesupporting
confidence: 82%
“…A recent work [10] has shown that over 60 variables for the Brazilian urban system are well described by a power-law equation of the form:…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Determining under which conditions scaling is correct is then a challenge for studies in this directions. Additionally, it has been recently suggested [85] that scaling exponents could experience time dependence and could converge to 'equilibrium' values, but more data are needed to test this assumption.…”
Section: Scaling and Individual Citiesmentioning
confidence: 99%